Pengaruh Motivasi, Pelatihan,dan Lingkungan Kerja terhadap Kinerja Karyawan Outsourcing pada Pt Bri, Tbk Kantor Wilayah Jakarta I - Siti Nurjanah; Eny Ariyanto (Telaah Bisnis, 2016)
AbstractThe research aims to identify the influence of motivation, training and the work environment on the performance of outsourced employees of PT BRI, Tbk Regional Office Jakarta 1. The sample of this research were employees of outsource PT BRI, Tbk Regional Office Jakarta 1. The research sample is consisted of 312 respondents which are determined by a census. Data of this research are obtained through questionnaire. The research methodology is descriptive and verificative methods using regression and correlation analysis of data. The result suggested variables of motivation, training and work environment either partially or simultaneously have influence positive significant toward the increasing employee performance. The finding shows that there is simultaneously 70.6% influence level of motivation, training and work environment on employee’s performance.